2019
DOI: 10.1002/nha3.20263
|View full text |Cite
|
Sign up to set email alerts
|

Women's experiences of workplace bullying: A content analysis of peer‐reviewed journal articles between 2000 and 2017

Abstract: Bullying has been a serious social issue in contemporary society. Traditionally, bullying has been examined in various social contexts and different populations including academic, community, and workplace settings. In recent years, although there has been an increasing number of publications about women's experiences of harassment and sexual assaults at work, there has not been much research that specifically focuses on women and women's experiences of workplace bullying. The purpose of this article was to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 48 publications
(64 reference statements)
2
9
0
Order By: Relevance
“…Research generally identifies men as more common perpetrators, with women more commonly targeted. 1,14,15 Our Kruskal-Wallis analysis of UWBQ-R data aligned with the literature, with women reporting more experiences of Hostility, Exclusionary Behavior, and Gossiping. Similarly, our logistic regression analysis of NAQ-R data revealed that women were more likely to report having experienced incivility in the last 6 months compared with men.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Research generally identifies men as more common perpetrators, with women more commonly targeted. 1,14,15 Our Kruskal-Wallis analysis of UWBQ-R data aligned with the literature, with women reporting more experiences of Hostility, Exclusionary Behavior, and Gossiping. Similarly, our logistic regression analysis of NAQ-R data revealed that women were more likely to report having experienced incivility in the last 6 months compared with men.…”
Section: Discussionsupporting
confidence: 77%
“…e prevalence of bullying and incivility has been examined in academia 6,9,10 as well as across clinical health care settings. [11][12][13] Across settings, women are more frequently targets of bullying and incivility than men, 1,14,15 and men are identified as perpetrators more frequently than women. 1,15 More novice members of a team are more likely to be targeted.…”
Section: Review Of Literaturementioning
confidence: 99%
“…This loss of confidence is confirmed in the literature (Valverde, 2013) as the “dark side” of transformative learning (Morrice, 2012). Women may personalize bullying more than men who see it as organizational (Misawa et al, 2017). However, several participants understood the structural department power dynamics that accounted for the bullying.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have universally concurred in demonstrating that most occurrences of WSH are perpetrated by men against women (Herrera et al, 2018; McDonald, 2012; Minnotte & Legerski, 2019; O’Leary-Kelly et al, 2009; Wei, 2016). They have also consistently shown that women typically use avoidance strategies to cope with WSH, including disengagement, withdrawal, and remaining silent (Lin & Yang, 2019; Misawa et al, 2019) and seldom make formal complaints, either through internal organizational procedures or to outside bodies (Fitzgerald et al, 1995; McDonald, 2012). There are many reasons why women choose to remain silent in the face of SH.…”
Section: From Avoidance To Confrontation: a Continuum Of Women’s Resp...mentioning
confidence: 99%